Design And Construction Of A C-Band Polarimetric Scatterometer - Koo , Voon Chet (1999)
A ground-based C-band scatterometer system has been constructed at the Faculty of Engineering, Multimedia University, Malaysia. This is a full polarimetric radar operating at 6Ghz frequency (5cm wavelength). The scatterometer is targeted for short range operation from 20 to 100 meter. It has the capability to determine complete backscattering matrix of various natural targets over a wide dynamic range (+20dB to -40dB). The system operates using frequency-modulated continuous-wave (FM-CW) technique. For short range radar, this is a simpler and more economical hardware design. In general, the system hardware consists of four major sections: an antenna, a radio frequency (RF) subsystem, and intermediate frequency ( IF) electronic, and a data acquisition unit (DAU). The antenna is a parabolic reflector with dual-polarised corrugated horn feed. The RF section is constructed in housefrom several RF components, which include a C-band voltage-controlled oscillator, directional coupler, circulator, RF switches, band-pass filter, isolators, and quadrature mixer. In RF section, the received signal is mixed with a portion of the transmitted signal to produce low frequency IF signals. The IF signals are pre-processed in IF section, before they are digitised in DAU. A microcomputer is used to store the measurement data. In addition, a dedicated computer program has been written to automate the measurement system and to analyse the collected data. Both internal and external calibrations are employed to eliminate short-term and long-term variations in the measurements, respectively. A 100ns delay line is incorporated in the hardware system for internal calibration. External calibration is accomplished by using the single-target calibration technique (STCT) proposed by Sarabandi and Ulaby (1990). With this technique, only a conducting sphere is needed to fully calibrate the radar for all polarisation combinations. The internal calibration is carried out for every measurement, while the external calibration is conducted only once in a controlled environment before conducting the actual field measurement. In May 1999, a series of controlled experiments has been conducted to evaluate the system performance. The test site is a typical football field. A styrofoam column, which has a dielectric constant close to that of the air, is used to support the test targets. The test targets include a non-depolarised 8" trihedral corner reflector, and a rotatable 4" X 8" dihedral corner reflector. The dihedral is rotated in different angles to provide different sets of polarimetric data. The measurement results show good agreement with the theory. This system will be used to conduct in situ backscatter measurement on earth terrain such as vegetation fields, forest and soil surfaces in the near future.